Cyclophosphamide, doxorubicin, vincristine and prednisone chemotherapy and radiotherapy for stage I intermediate or high grade non-Hodgkin's lymphomas: results of a strategy that adapts radiotherapy dose to the response after chemotherapy - Krol, Augustinus D.G; Berenschot, Henriëtte W.A; Doekharan, Dew; Henzen-Logmans, Sonja; van der Holt, Bronno; van ‘t Veer, Mars B (Radiotherapy and oncology, 2001)
Background: A limited number cycles of cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) chemotherapy followed by involved field radiotherapy is the treatment of choice for Ann Arbor stage I intermediate or high grade non-Hodgkin's lymphomas (NHL). The optimal radiotherapy dose in this combined modality setting, resulting in maximal disease control with minimal toxicity is unknown. In this retrospective single-center study we evaluated the results of a combined modality treatment strategy that adapts the radiotherapy dose to the response after chemotherapy, and focus on the influence of radiotherapy dose on local control and survival. Patients and methods: One hundred and forty patients with NHL Ann Arbor stages I/IE of intermediate or high grade malignancy received four cycles of CHOP chemotherapy followed by involved field radiotherapy (IF-RT). The radiotherapy dose for patients in complete response (CR) after CHOP was either 26 or 40 Gy. Patients in partial response (PR) after CHOP always received 40 Gy. The influence of the radiotherapy dose on treatment outcome was evaluated for patients in CR at the end of treatment ( n=128). Results: CR rates after chemotherapy and after radiotherapy were 67 and 91%, respectively. Seventy-four of the patients in CR after CHOP received 26 Gy, 20 patients in CR after CHOP 40 Gy. All patients in PR after CHOP ( n=34) received 40 Gy. The localization of relapse (within or outside the radiation field) did not differ between patients receiving 26 or 40 Gy. Overall survival (OS) at 5 years for patients in CR after CHOP who received 26 and 40 Gy and for patients in PR after CHOP but CR after 40 Gy IF-RT was 76, 100 and 75%, respectively, ( P=0.16), disease free survival (DFS) at 5 years 69, 90 and 75%, respectively, ( P=0.52). Conclusions: No statistically significant differences in patterns of relapse or survival were found between patients receiving 26 or 40 Gy IF-RT, however the number of events in all subgroups was small.